Effects of prenatal subjective well-being on birth outcomes and child development: A longitudinal study. Issue 1 (4th November 2022) - Estinfort, Wanda; Huang, Jian-Pei; Au, Heng-Kien; Lin, Chen-Li; Chen, Yi-Yung; Chao, Hsing Jasmine; Chien, Ling-Chu; Lo, Yu-Chun; Chen, Yi-Hua
Abstract: Background: Although maternal mental illnesses have been found to influence child health and development, little is known about the impact of maternal positive well-being on child health and development. Therefore, this longitudinal study investigated the effects of prenatal subjective well-being on birth outcomes and child development by considering the potential modifier effect of parity. Methods: Pregnant women in early stages of pregnancy were recruited at five selected hospitals in Taipei, Taiwan, during their prenatal appointments since 2011. Self-reported evaluations were conducted at seven time points up to 2 years postpartum. Linear regression and generalized estimating equation models were used for examination. Results: Higher prenatal eudaimonic well-being was associated with longer gestational length (adjusted beta [aβ] = 0.36, 95% confidence interval [CI] = 0.03, 0.68) and higher birth weight (aβ = 124.71, 95% CI = 35.75, 213.66). Higher positive and negative affect were associated with longer gestational length (aβ = 0.38, 95% CI = 0.06, 0.70) and smaller birth weight (aβ = −93.51, 95% CI = −178.35, −8.67), respectively. For child's outcomes, we found an association between higher prenatal eudaimonic well-being and decreased risks of suspected developmental delay, particularly for children of multiparous mothers (adjusted odds ratio = 0.18, 95% CI = 0.05, 0.70). Higher levels of prenatal depression and anxiety were significantly associated with increased risks of suspected developmental delay for children of primiparous mothers. Conclusions: Positive prenatal maternal mental health may benefit birth outcomes and child development, particularly for children of multiparous mothers. Interventions for improving prenatal mental health may be beneficial for child development.